Economía artificial: Una valoración crítica - Segismundo S. Izquierdo; Luis R. Izquierdo; José M. Galán; José I. Santos (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– Artificial Economics is one of the fastest growing approaches to analyse complex socio-economic systems. In this paper we present our views on the distinguishing features of Artificial Economics and on its relation with Theoretical Economics - the field that in our opinion lies closest to Artificial Economics. In this context, we discuss various reasons why conducting research on Artificial Economics may be worthwhile, and provide general guidelines on how to go about it. Our view is that Artificial Economics and Theoretical Economics share the same goals, do not differ conceptually as much as it is sometimes perceived, and their approaches are certainly complementary.
Keywords: B41; C15; C63; 330; artificial economics; computational economics; agent-based computational economics